Epidemiological features of Ixodic tick-borne Borreliosis in children in the Ulyanovsk region - A. A. Nafeyev; T. M. Bergelson; A. A. Nafeyeva (Детские инфекции (Москва), 2019)
This paper presents materials on the incidence of children with ixodiс tick-borne borreliosis in the Ulyanovsk region for the period 1996—2017.28 cases of tick-borne borreliosis among children were recorded. Tick suction in April-May was observed in 6 (21.4%) children, in June—August — in 12 (42.9%), in September—November — in 10 (35.7%). Migratory erythema was detected in 15 patients (53.6%). In half of the cases, moderate intoxication symptoms were observed (57.1%). Borreliosis was confirmed laboratory early in 75% of cases.Thus, a feature of ixodiс tick-borne borreliosis in children in the Ulyanovsk region is: detection of the disease during the period of tick activity, that is, in the early stages; equal ratio of erythema and non-erythhema forms; the prevalence in the clinic of mild symptoms of intoxication; laboratory confirmation in 75% of cases in the early stages. The presence of migratory erythema in the patient gives reason for the diagnosis of ixodiс tick-borne borreliosis even in the absence of positive results of a serological examination.